Synthesis of Ag and AgCl co-doped ZIF-8 hybrid photocatalysts with enhanced photocatalytic activity through a synergistic effect. Issue 2 (2nd January 2020) - Jing, Yanqiu; Lei, Qiang; Xia, Chun; Guan, Yu; Yang, Yide; He, Jixian; Yang, Yang; Zhang, Yonghui; Yan, Min
Abstract : Recently, Ag/AgCl composites with different structures have been widely studied and used as photocatalysts to degrade dye pollutants, due to their high separation efficiency of electron–hole pairs under visible light irradiation. Abstract : Recently, Ag/AgCl composites with different structures have been widely studied and used as photocatalysts to degrade dye pollutants, due to their high separation efficiency of electron–hole pairs under visible light irradiation. Herein, we adopted a nucleation, precipitation, growth and photoreduction method to prepare Ag and AgCl co-doped ZIF-8 hybrid photocatalysts and explored the influence of Ag content on their physical and chemical properties. All as-prepared samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Brunauer–Emmett–Teller (BET) measurements, energy dispersive spectroscopy (EDS), UV-vis diffuse reflectance and X-ray photoelectron spectroscopy (XPS). XRD indicated that ZIF-8 and AgCl were formed and some of the AgCl was reduced into Ag 0 after 30 min of UV light irradiation. SEM and TEM images verified that Ag/AgCl nanoparticles were inlaid in the body of ZIF-8 and Ag ions could hinder the growth of the ZIF-8 crystal. BET data indicated that Ag/AgCl nanoparticles did not alter the pore size of ZIF-8. The UV-vis diffuse reflectance spectra showed that Ag/AgCl@ZIF-8 has excellent ability to absorb visible light, indicating the high efficiency of the electron–hole pair separation of Ag/AgCl@ZIF-8. Finally, the photocatalytic activities of all of the as-synthesized samples were evaluated by degradation of RhB under visible light irradiation. Ag and AgCl co-doped ZIF-8 hybrid photocatalysts exhibited high photocatalytic activity due to the synergistic effect of ZIF-8, AgCl and Ag. After 60 min of visible light irradiation, Ag/AgCl(15)@ZIF-8 exhibited the best photocatalytic activity and could degrade 99.12% RhB, which was higher than Ag/AgCl (94.24%) and ZIF-8 (5.17%). Additionally, a photocatalytic mechanism for dye pollutant degradation over the Ag and AgCl co-doped ZIF-8 hybrid photocatalysts was proposed.